Análisis De Políticas Y Procedimientos Contables De La Compañía Aldastructure - Murillo Morante, Mixy Melissa (2018)
The construction entities are characterized as being companies that receive resources monetary measures on the part of their shareholders to be employed in the preparation of works to through works contracts, that is, they are basically integrated by capital and work in order to offer an optimal service for the common good. The present case study work will deal with POLICY ANALYSIS AND ACCOUNTING PROCEDURES, it was done in THE COMPANY ALDASTRUCTURE S.A., where the procedures, rules and policies were examined For the proper functioning of the company's accounting system, this investigation will be considers qualitative, and is under the research sub-line of the Engineering Degree in Accounting and Auditing: Accounting Information Management the Technical University of Babahoyo in the Faculty of Administration, Finance and Computing. The main purpose of this company is the construction of its own works. civil engineering this is the study, design, planning, construction, exploitation and business administration, consulting activities for civil engineering projects and architecture, roads, streets, and other roads for vehicles or pedestrians. The importance of this issue arises because the company ALDASTRUCTURE S.A. of the city of Babahoyo, according to researches made to the staff administration through dialogue, it became evident that it lacks policies and adequate accounting procedures, which directly affects the accounting system of said company in view of the fact that it began its activities on September 4, 2017, it has been in operation for a short time and does not have adequate procedures for register and accounting control.